Discovery of novel falcipain 2 inhibitors by in silico guided drug repositioning - Alberca, Lucas Nicolás (2019)
Malaria is a life-threatening condition that continues being one of global leading causes of death worldwide, being themain cause of death globally in the 5-14 year-old population. The disease is caused by parasites from the Plasmodiumgenre. The emergence of Plasmodium falciparum resistant strains with reduced sensitivity to the first linecombination therapy have led to renewed interest in novel therapeutic options. In this work, our objective was theidentification of novel Falcipan-2 (FP2) inhibitors through the application of an in silico approach and the subsequentin vitro evaluation of the emerging hits. FP2 is a key cysteine protease in the life cycle of P. falciparum constituting apromising target in the search for novel therapies due to their significant hemoglobinase capacity.We have developed a ligand-based model ensemble capable of recognizing FP2 inhibitors from non-inhibitors. Thisensemble has showed a powerful ability for the identification of FP2 inhibitors. The ensemble was applied in a virtualscreening campaign of DrugBank database to identify approved drugs with FP2 inhibitory activity. 4 hits wereacquired and tested against recombinant FP2 using a fluorogenic continuous enzymatic assay under balanced assayconditions ([S]0/KM=1). The reversibility of the interaction, mode of inhibition and Ki were further investigated forvalidated hits. Two drugs, Methacycline and Odanacatib, showed dose-dependent inhibition of FP2. Although bothinhibitors showed reversible interactions with FP2, the compounds displayed different inhibition mechanisms. Doseresponseanalysis at growing substrate concentrations indicated that Odanacatib is a competitive inhibitor of FP2(Ki=98.2 nM), whereas Methacycline displayed non-competitive behaviour (Ki=84.4 μM; α =1.42) being to our bestknowledge the first report of the inhibition of plasmodial cysteine proteases by a tetracycline derivative in a noncompetitivemanner. To access the impact of Methacycline and Odanacatib on the intracellular parasite?sdevelopment, parasite trophozoite forms were treated with the compounds for 48h and the parasitemia was analyzedby light microscopy. Treatment of infected erythrocytes with the compounds caused inhibition in a dose-dependentmanner. These results demonstrate the utility of the in silico approach, since we could find two FP2 inhibitors withantiplasmodial activity with a minimal investment of time and money.